Outcomes of Integrase Inhibitor–based Antiretroviral Therapy in a Clinical Cohort of Treatment-experienced Children, Adolescents and Young Adults With HIV Infection. Issue 5 (May 2020) - Levy, Matthew E.; Griffith, Caleb; Ellenberger, Nicole; Monroe, Anne K.; Castel, Amanda D.; Rakhmanina, Natella
Abstract : Background: Data on integrase strand transfer inhibitor (INSTI) use in children, adolescents and young adults with HIV are limited. We evaluated virologic and safety outcomes following INSTI initiation among treatment-experienced children, adolescents and young adults. Methods: The DC Cohort is a multicenter observational study of individuals receiving HIV care in Washington, DC. This analysis included treatment-experienced participants 0–24 years of age who initiated an INSTI during 2011–2017. Viral suppression (VS) and safety outcomes were quantified. Differences in VS by age, sex and CD4 count were assessed using Kaplan-Meier curves. Results: Of 141 participants (median age 20 years; 35% <18 years; 60% male; 89% Black; 62% perinatally-infected), 35% had VS and 65% lacked VS on INSTI initiation. Dolutegravir was the most commonly prescribed INSTI (55%). Among participants without VS at INSTI initiation, 46% achieved VS after a median of 2.7 months. Participants 13–24 (vs. 0–12) years old ( P = 0.011) and participants with CD4 counts <350 (vs. >500) cells/μL were less likely to achieve VS ( P < 0.001). Among participants with VS at INSTI initiation, 51% sustained VS through a median of 11.0 months of follow-up; of the 49% with transient viremia, 77% later achieved VS again. There were no safety concerns associated with the use of INSTIs. Conclusions: More than half of treatment-experienced children, adolescents and young adults with detectable viremia at INSTI initiation did not achieve VS, while half of those with prior VS experienced transient viremia. Further evaluation of long-term outcomes associated with INSTI use among children, adolescents and young adults is warranted. Abstract : Supplemental Digital Content is available in the text.